Characterizing Coin-Based Voting Governance in DPoS Blockchains - Li, Chao; Xu, Runhua; Duan, Li (Proceedings of the International AAAI Conference on Web and Social Media, 2023)
Delegated-Proof-of-Stake (DPoS) blockchains are governed by a committee of dozens of members elected via coin-based voting mechanisms. This paper presents a large-scale empirical study of two critical characteristics, personal impact and participation rate, of three leading DPoS blockchains. Our findings reveal the existence of decisive voters whose votes can alter election outcomes, as well as the fact that almost half of the coins have never been used in committee elections. Our research contributes to demystifying the actual use of coin-based voting governance and offers novel insights into the potential security risks of DPoS blockchains.